Prevalence of pathogenic bacteria in Ixodes ricinus ticks in Central Bohemia - Klubal, Radek; Kopecky, Jan; Nesvorna, Marta; Sparagano, Olivier A E; Thomayerova, Jana; Hubert, Jan (Experimental & applied acarology, 2016)
Bacteria associated with the tick Ixodes ricinus were assessed in specimens unattached or attached to the skin of cats, dogs and humans, collected in the Czech Republic. The bacteria were detected by PCR in 97 of 142 pooled samples including 204 ticks, i.e. 1-7 ticks per sample, collected at the same time from one host. A fragment of the bacterial 16S rRNA gene was amplified, cloned and sequenced from 32 randomly selected samples. The most frequent sequences were those related to Candidatus Midichloria midichlori (71% of cloned sequences), followed by Diplorickettsia (13%), Spiroplasma (3%), Rickettsia (3%), Pasteurella (3%), Morganella (3%), Pseudomonas (2%), Bacillus (1%), Methylobacterium (1%) and Phyllobacterium (1%). The phylogenetic analysis of Spiroplasma 16S rRNA gene sequences showed two groups related to Spiroplasma eriocheiris and Spiroplasma melliferum, respectively. Using group-specific primers, the following potentially pathogenic bacteria were detected: Borellia (in 20% of the 142 samples), Rickettsia (12%), Spiroplasma (5%), Diplorickettsia (5%) and Anaplasma (2%). In total, 68% of I. ricinus samples (97/142) contained detectable bacteria and 13% contained two or more putative pathogenic groups. The prevalence of tick-borne bacteria was similar to the observations in other European countries.
Keywords: Animals; Spiroplasma; Cities; Female; klíště; polymerázová řetězová reakce; Polymerase Chain Reaction; ženské pohlaví; DNA bakterií; Ixodes ricinus; nymfa; velkoměsta; RNA, Ribosomal, 16S; Pathogens; DNA, Bacterial; lidé; Molecular Sequence Data; kočky; Tick; Dogs; Nymph; Cats; Phylogeny; molekulární sekvence - údaje; Male; Bacteria; Czech Republic; Česká republika; zvířata; mužské pohlaví; fylogeneze; Central Bohemia; RNA ribozomální 16S; psi; Ixodes; Humans